A Bibliometric Analysis of Lodging-Context Research From 1990 to 2016. (February 2019) - Okumus, Fevzi; Köseoglu, Mehmet Ali; Putra, Eka Diraksa; Dogan, Ismail Cagri; Yildiz, Mehmet
This study evaluates lodging-context research by addressing the trend in the number of journal publications and the most prolific contributors from 1990 to 2016. To this end, data were collected from 16 leading academic journals. The study results suggest that the number of lodging-context articles from 1990 to 2016 increased significantly and that among the 16 leading journals analyzed, the International Journal of Hospitality Management and the International Journal of Contemporary Hospitality Management were the two most productive journals in publishing lodging-context–related articles. Contributors were identified according to author, institution, and country. Regarding lodging operations classifications, hotels appeared to be the most researched organizations while marketing was found to be the most studied research topic, followed by strategic management. This is the first study offering a bibliometric analysis of lodging-context research in our field.